2020
DOI: 10.3171/2019.12.focus19841
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a synthetic 3D-printed simulator for training in neuroendoscopic ventricular lesion removal

Abstract: OBJECTIVENeuroendoscopic surgery using an ultrasonic aspirator represents a valid tool with which to perform the safe resection of deep-seated ventricular lesions, but the handling of neuroendoscopic instruments is technically challenging, requiring extensive training to achieve a steep learning curve. Simulation-based methods are increasingly used to improve surgical skills, allowing neurosurgical trainees to practice in a risk-free, reproducible environment. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 24 publications
0
20
0
Order By: Relevance
“…Clearly, a learning curve for the technically challenging use of the NUA exists, thus not excluding the successful resection of larger lesions with increasing experience. To this purpose, the development of teaching models for endoscopy and NUA use additionally supports the training without the involvement of patients [10]. So far, our recommendation would be to tailor the approach (burr hole vs. mini-craniotomy in combination with a speculum) according to the surgeon's experience, the size of the lesion, and its characteristics (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, a learning curve for the technically challenging use of the NUA exists, thus not excluding the successful resection of larger lesions with increasing experience. To this purpose, the development of teaching models for endoscopy and NUA use additionally supports the training without the involvement of patients [10]. So far, our recommendation would be to tailor the approach (burr hole vs. mini-craniotomy in combination with a speculum) according to the surgeon's experience, the size of the lesion, and its characteristics (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that 3DP models with tactile sensation play an active role in the process of learning complex structures, such as acetabular fractures, liver structures, and craniovertebral junction deformities ( 19 , 21 , 26 ). Licci et al introduced a synthetic 3DP simulator which allowed trainees to develop skills for endoscopic ventricular lesion removal ( 23 ). The authors evaluated the validity of the 3DP model in term of realism, mechanical proprieties, procedural content, and handling.…”
Section: Discussionmentioning
confidence: 99%
“…The tangible 3DP models may improve learning efficacy by providing tactile feedback. VR and 3DP models have been used in many clinical specialties for advanced teaching, preoperative planning, and simulated surgery (14,(18)(19)(20)(21)(22)(23). However, the effectiveness of VR and 3DP models in learning to perform SSRO remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, FFF technology, the most accessible AM method, is already implemented in the hospitals for the fabrication of anatomical bio‐models, customized surgical instruments, and prosthetic aids 19,20 . While these applications have typically been achieved with low temperature polymers, recent technological advancements in FFF 3D printers have made it possible to process high‐temperature thermoplastic materials such as PAEK.…”
Section: Introductionmentioning
confidence: 99%